Evaluation of the relationship between sociodemographic characteristics, quality of life, depression, drug compliance and biochemical parameters in patients with thalassemia major in Isparta (Annals of Medical Research, 2021)
Aim: We aimed to evaluate the quality of life and depression levels of BTM patients in our unit, to determine the relationship between each parameter and evaluate the demographic characteristics, laboratory data, and treatment compliance.Materials and Methods: Twenty-seven BTM patients aged 18 years and over were included in the study. Sociodemographic data were collected from the patients with a data form. Laboratory data were obtained from hospital records retrospectively. The patients were asked to respond to the BDI and SF-36 content in which depression was questioned and quality of life was evaluated respectively. The relationship between each parameter was examined.Results: 70,3 % of the patients had minimal-mild and 11,1 % of the patients had severe depression. Depression levels were significantly higher in patients who had a regular job and who had poor compliance to chelation therapy. Physical function and physical role subscales of single patients were significantly higher than married patients. Patients with monthly income had higher quality of life in terms of physical role, mental health, social functioning and pain subscales. The patients without co-morbidity had higher quality of life in terms of physical role, pain and general health subscales. Patients with severe depression had the worst quality of life. The general health perception of patients with minimal depression was higher than those with moderate depression and severe depression.Conclusions: Psychosocial support of patients is important and, therapy should be aimed not only to ensure long life without complications but also improve the quality of life of the patients.